Potential of using non‐inoculated self‐aerated immobilized biomass reactor for post‐treatment of upflow anaerobic staged reactor treating high strength industrial wastewater. Issue 5 (5th October 2016) - Ali, Manal; Farghaly, Ahmed; Roux, Sophie Le; Peu, Pascal; Dabert, Patrick; Tawfik, Ahmed
Abstract: BACKGROUND: The cake industry produces a heavily polluted wastewater that is characterized by high amounts of suspended solids, lipids, chemical oxygen demand (COD), biochemical oxygen demand (BOD5 ) and nitrogen components. In this study, assessment of the efficiency of a non‐inoculated self‐aerated immobilized biomass (SAIB) reactor for post‐treatment of the anaerobic effluent of cake processing wastewater was extensively investigated. RESULTS: The reactor was operated at different hydraulic retention times (HRTs) and sludge residence times (SRTs). CODt and CODs removal efficiencies increased from 50 ± 15.2 to 61.8 ± 20.7% and from 51.6 ± 9.3 to 60 ± 17.8% on increasing the HRT from 2.5 to 5.0 h, respectively. Maximum nitrification efficiency and biomass concentration of 67% ± 3.1% and 39.8 gVS L −1 sponge was obtained at an SRT of 42 days. The results of an empirical model showed good agreement between predicted and experimental values. Ammonium oxidizing bacteria (AOB) was dominated and represented 0.14% at the middle zone of the reactor where the dissolved oxygen is sufficient for growth of nitrifiers. CONCLUSION: The innovative SAIB reactor was able to treat cake wastewater with high content of carbon and lipids in comparison with other conventional technologies. The efficiency of the reactor was contingent mainly on HRT, SRT, VSS/TSS ratio, F/M ratio and CODp/CODt ratio. © 2016 Society of Chemical Industry